Evaluation of Clinical Knowledge Regarding Geriatric Skin Conditions among Thai Physicians - Chanyachailert P. (2023)
Objective: Assess the knowledge of common geriatric skin conditions in Thai physicians. Materials and Methods: This retrospective study was conducted among Thai physicians attending annual dermatology courses by the Dermatological Society of Thailand from 2016 to 2019. Data was assessed based on knowledge of diagnosis and management of common geriatric skin conditions. Results: A total of 197 participants, mainly general practitioners, were included. The highest percentage of correct diagnoses were benign erythematous, eczematous lesions (35.5%, senile purpura; 36.0%, xerotic eczema), and malignant diseases (35.5%, basal cell carcinoma; 27.4%, squamous cell carcinoma; 11.7%, subungual melanoma; 24.4%, acral lentiginous melanoma). In contrasts, the lowest percentage of correct diagnosis were premalignant diseases (0.5%, arsenical keratosis; 4.6%, actinic keratosis; 1.0% Bowen’s disease) and benign hypopigmented lesion (0.5%, stellate pseudoscar; 7.6%, idiopathic guttate hypomelanosis). Harmful treatment with systemic antifungal therapy was used in subungual melanoma (58.0%). Harmful management of senile comedone, subungual melanoma and acral lentiginous melanoma was significantly found in physicians given the incorrect diagnosis. (p = 0.027, p <0.001, p = 0.014, respectively). Conclusion: Most physicians recognized malignant lesions, benign erythematous or eczematous diseases in elderly skin. Surprisingly, almost all physicians couldn’t diagnose premalignant lesions and benign hypopigmented lesions